Mitigating Student’s Stage Fright in Public Speaking at An Islamic Boarding School in Samarinda - Salsabila, Nala; Rachman, Dzul (Borneo Educational Journal (Borju), 2025)
Delivering a speech or presentation to an audience is known as public speaking. In general, oral interaction with a wide audience intended to transmit ideas, messages, and opinions is referred to as public speaking. This qualitative study investigates how students at an Islamic boarding school navigate stage fright in public speaking, particularly when using English as a foreign language. The study explores the methods students use to deal with stage fright, the effect that social support has on anxiety control, and the differences between stage fear in academic and non-academic environments. Through in-depth interviews with students from a high school in Samarinda, the study sheds light on students' perspectives and coping mechanisms concerning stage fright during public speaking engagements.